Zoonotic diseases: who gets sick, and why? Explorations from Africa - Dzingirai, V.; Bett, Bernard K.; Bukachi, S.A.; Lawson, E.; Mangwanya, L.; Scoones, Ian; Waldman, L.; Wilkinson, A.; Leach, M.; Winnebah, T.R.A. (Informa UK Limited, 2017)
Global risks of zoonotic disease are high on policy agendas. Increasingly, Africa is seen as a ‘hotspot’, with likely disease spillovers from animals to humans. This paper explores the social dynamics of disease exposure, demonstrating how risks are not generalised, but are related to occupation, gender, class and other dimensions of social difference. Through case studies of Lassa Fever in Sierra Leone, Henipah virus in Ghana, Rift Valley Fever in Kenya and Trypanosomiasis in Zimbabwe, the paper proposes a social difference space–time framework to assist the understanding of and response to zoonotic diseases within a ‘One Health’ approach.